2015
DOI: 10.1002/lno.10102
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving the algae: How feeding‐current feeding copepods detect their nonmotile prey

Abstract: Feeding‐current feeding copepods detect and capture prey individually, but the mechanism by which nonmotile prey is detected has been unclear. Early reports that copepods detect phytoplankton prey at distances of one body length or more led to the hypothesis that solutes leaking from the prey would be carried to the copepod by the sheared feeding current and arrive prior to the prey, thus allowing the copepod to adjust the feeding current to bring the prey within reach of the feeding appendages. Many subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 66 publications
4
38
0
Order By: Relevance
“…We argue that chemical detection is neither required nor likely for remote detection at such short distances. First, the ∼ 100 μ m detection distance for a 45‐ μ m sized prey cell reported here is in fact similar to that predicted (50–200 μ m) by mechanoreception and the fluid mechanical mechanisms examined by Gonçalves and Kiørboe (). Second, the chemosensory apical pores on the setae of the feeding appendages, as found in copepods (Paffenhofer and Loyd ) and many other crustaceans, are normally considered to have gustatory (taste) rather olfactory (smell) function; i.e., they only mediate chemical signals upon direct contact with the source (Hallberg and Skog ).…”
Section: Concentration Matters?supporting
confidence: 89%
See 2 more Smart Citations
“…We argue that chemical detection is neither required nor likely for remote detection at such short distances. First, the ∼ 100 μ m detection distance for a 45‐ μ m sized prey cell reported here is in fact similar to that predicted (50–200 μ m) by mechanoreception and the fluid mechanical mechanisms examined by Gonçalves and Kiørboe (). Second, the chemosensory apical pores on the setae of the feeding appendages, as found in copepods (Paffenhofer and Loyd ) and many other crustaceans, are normally considered to have gustatory (taste) rather olfactory (smell) function; i.e., they only mediate chemical signals upon direct contact with the source (Hallberg and Skog ).…”
Section: Concentration Matters?supporting
confidence: 89%
“…While it is well established that ambush feeders perceive their prey by the fluid mechanical disturbance that the swimming prey generates (Jonsson and Tiselius ; Yen and Strickler ; Svensen and Kiørboe ; Jiang and Paffenhöfer ), the mechanism and distance at which feeding‐current feeding copepods can detect non‐motile prey remains a controversial issue. In a series of recent studies involving six different species as well as several developmental stages we observed that in all cases, prey had to be in the immediate vicinity of the feeding appendage setae in order to elicit a capture response (Bruno et al ; Kjellerup and Kiørboe ; Tiselius et al ; Gonçalves et al ; Gonçalves and Kiørboe ). We also reviewed all available evidence of prey perception and found that, in most cases, cells as well as inert plastic particles were detected within a few prey cell radii from the setae of the feeding appendages (Gonçalves and Kiørboe ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schultz and Kiørboe (2009) suggested that copepods possess the ability to remotely discriminate non-toxic and toxic algae before capture. Recently however the ability of copepods to remotely detect phytoplankton based on their chemical characteristics has been questioned (Gonçalves and Kiørboe, 2015), and our observations suggest that prey selection is based on post-capture discrimination and that unwanted cells are rejected following a handling time. Vanderploeg et al (1990) reported a similar observation in a freshwater copepod.…”
Section: Repertoire Of Copepod Feeding Behaviors and Implications To mentioning
confidence: 82%
“…Due to their small size, many phytoplankton species with diameters < 5 µm are not typically considered to be important food sources for copepods, which frequently exhibit prey choice based on size (Sommer et al 2000) or swimming behavior (Kiørboe & Visser 1999), and even chemical cues in the case of larger aggregates (Goncalves & Kiørboe 2015). The high-latitude hapto phyte Phaeocystis spp.…”
Section: Introductionmentioning
confidence: 99%